Efficiency of CO2 fixation by microalgae in a closed raceway pond - Li, Shuwen; Luo, Shengjun; Guo, Rongbo (Bioresource technology, 2013)
•A closed raceway pond and its equation of CO2 mass transfer.•CO2 dissolution efficiency in the closed raceway pond without algae.•CO2 fixation efficiency by algae with continuous aeration in the pond.•A mode of intermittent aeration with CO2 fixation efficiency of 95% in the pond. Microalgae contain about 50% of carbon, which means that a total of 1.83ton of CO2 is needed to produce 1ton of microalgae. The cost of CO2 supply for microalgal large scale cultivation should be considered and the low CO2 fixation efficiency by microalgae will lead to much more expenditure of CO2. In this study, a closed raceway pond was constructed by covering a normal open raceway pond with a specially designed transparent cover, which directly touched the surface of microalgal culture media. This cover prevented supplied CO2 escaping into atmosphere and thus increased the retention time of CO2. The CO2 gas–liquid mass transfer and CO2 fixation efficiency by microalgae in the closed raceway pond were investigated, and the model of CO2 fixation by microalgae was developed. Through the model, the CO2 fixation efficiency increased to 95% under intermittent gas sparging.